PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE TRUE FALSE CHAIN UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA POKOK BAHASAN REAKSI REDOKS KELAS X SMA NEGERI 4 PEKANBARU - Dewi Sumarlina; Miharty '; Betty Holiwarni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
An experimental research on the application of the active learning strategy typetrue false chain has been concluded to investigate the improvement of studentlearning outcomes on the subject of the oxidation-reduction reaction in class XSMA Negeri 4 Pekanbaru. From three classes of the population, it was taken twoclasses as the homogeneous samples, i.e. X.8 and X.7. The X.8 class was a controlclass in which they were used to teach by conventional teaching and learningprocess, while the X.7 class was taken as the experimental class in which theywere given the treatment of the active learning strategies type True False Chainimplementation. The data of the research was gathered by using testingtechniques, namely the pre-test and post-test. Before the pre-test and post-test, thesamples were tested by using a homogeneity test of homogeneity through T-test ofthe two parties in order to obtain two homogeneous classes. The difference inpretest-posttest values was analyzed by using two T-test samples of the party thataimed to test the truth of the hypothesis. Based on the results obtained bystatistical calculation that tvalue> ttable (2.070> 1.67), so it can be concluded thatthe application of active learning strategies type True False Chain can improvestudents’ learning outcomes on the subject of oxidation-reduction reactions inclass X of SMA Negeri 4 Pekanbaru.Keywords: Active Learning Strategy, True False Chain, Oxidation ReductionReaction.